2023
DOI: 10.3390/antibiotics12061071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phenylalanine–Arginine Beta-Naphthylamide on the Values of Minimum Inhibitory Concentration of Quinolones and Aminoglycosides in Clinical Isolates of Acinetobacter baumannii

Abstract: (1) Background: Acinetobacter baumannii has become the most important pathogen responsible for nosocomial infections in health systems. It expresses several resistance mechanisms, including the production of β-lactamases, changes in the cell membrane, and the expression of efflux pumps. (2) Methods: A. baumannii was detected by PCR amplification of the blaOXA-51-like gene. Antimicrobial susceptibility to fluoroquinolones and aminoglycosides was assessed using the broth microdilution technique according to 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…Our study showed that SSB-3, SSB-4, or EA in combination with IMP or AMK showed antibiotic-modulating activity on UIMY-ABA-5 or UIMY-ABA-16, respectively [ 56 , 57 ]. The significant antibiotic-modulation threshold was set at a decrease of more than two-fold in the MIC of the tested antimicrobial, which is referred to as AMF [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that SSB-3, SSB-4, or EA in combination with IMP or AMK showed antibiotic-modulating activity on UIMY-ABA-5 or UIMY-ABA-16, respectively [ 56 , 57 ]. The significant antibiotic-modulation threshold was set at a decrease of more than two-fold in the MIC of the tested antimicrobial, which is referred to as AMF [ 58 ].…”
Section: Discussionmentioning
confidence: 99%